2013
DOI: 10.1038/jhh.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation does not influence arterial stiffness and pulse-wave velocity in patients with coronary artery disease

Abstract: Vascular function is an important pathophysiological factor in cardiovascular disease, and is influenced by many factors, one of the principles being hypertension. Developing evidence suggests that inflammation may be another risk factor. Vascular function and blood pressure haemodynamics can be assessed by arterial stiffness, pulse pressure and plasma markers. Testing the hypothesis of a relationship between inflammatory markers, hypertension and vascular function, we recruited 222 stable coronary artery dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Peripheral vascular dysfunction has been reported to be influenced by many factors including adiposity [ 17 ], blood pressure [ 18 ], age [ 18 ], physical activity [ 19 ] and inflammatory biomarkers such as C-reactive protein [ 20 ], which are also associated with pulmonary function. Thus the association between vascular dysfunction and pulmonary function could be influenced by, or depend on these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral vascular dysfunction has been reported to be influenced by many factors including adiposity [ 17 ], blood pressure [ 18 ], age [ 18 ], physical activity [ 19 ] and inflammatory biomarkers such as C-reactive protein [ 20 ], which are also associated with pulmonary function. Thus the association between vascular dysfunction and pulmonary function could be influenced by, or depend on these factors.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation of arterial stiffness, as a marker of early atherosclerosis, with the severity of systemic inflammation has been studied [31,32], but the studies are not consistent. Blann et al [31] found that arterial stiffness was not related to inflammation. But his research was conducted among patients with stable coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…[38]. However, two recent studies suggest that both systemic and vascular inflammation are not major determinants of arterial stiffness as measured by AI [39, 40]. Furthermore, the median baseline peripheral AI value of 11.9 in our cohort was approximately half the mean value of 21.4 measured using the EndoPAT device in a cohort of healthy black Americans, and the increase in AI we observed may represent a return to a more normal physiologic state on ART rather than a pathologic stiffening of the vasculature related to cardiovascular disease [19].…”
Section: Discussionmentioning
confidence: 99%